The Students' Perception towards Blended Learning in EFL Classroom during Pandemic - Haenur, Harclinda; Syamsinar, Syamsinar; Marliana, Rina (STAIN Majene, 2023)
This research aims to determine the students’ perception of Blended Learning in the EFL Classroom during COVID-19 pandemic. The researcher used a mixed method (qualitative and quantitative) as a research design. The researcher was collected the data from two schools in Majene regency. The result of this study shows that the students’ perceptions in Majene Regency were categorized as “undecided” toward Blended Learning from the questionnaire and interview results. The questionnaire result proved it reached a percentage 68.68%, and it was categorized as undecided based on the score category of the questionnaire in the Likert Scale. Then in the interview result, most students had a tendency to give a positive perception toward offline learning, otherwise, they preferred to give a negative perception toward online learning.